The Role of Telemedicine in Emergency Medical Services in Remote Areas of West Nusa Tenggara: An Evaluative Study - Atmaja, Hadi Kusuma; Luthfia, Erien; Haryati, Ani; Hasbi, Muhammad; Andrayani, Lale Wisnu; Sundayani, Lina (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2024)
In many countries, including Indonesia, access to emergency medical services remains a significant challenge, especially in remote areas. Telemedicine technology is expected to be an effective solution for improving accessibility and the quality of emergency services. this research aims to provide a comprehensive overview of the implementation of telemedicine in emergency medical services in remote areas at Lombok Island, West Nusa Tenggara. The research procedure is structured into several main stages, including planning, data collection, data analysis, and reporting. Data is collected through participatory observation, in-depth interviews with stakeholders such as healthcare workers and the local community, as well as document analysis related to the implementation of telemedicine. The results showed that telemedicine significantly improves accessibility, allowing residents to obtain medical consultations without having to travel long distances, thereby reducing the time and cost of receiving timely services. Furthermore, telemedicine enhances response time and coordination between field medical teams and health service centers, enabling more accurate diagnoses and effective management of emergencies. However, this research also reveals several challenges in the implementation of telemedicine, including limited technological infrastructure and a lack of trained personnel in using telemedicine technology. To optimize the implementation of telemedicine, efforts are needed to strengthen technological infrastructure and enhance the capacity of medical personnel in remote areas. Thie study Â research recommend several inputs for the development of policies and practices to enhance the effectiveness and inclusiveness of emergency medical services through telemedicine.